PENGARUH METODE PEMBELAJARAN CERAMAH DIBANDING DEMONSTRASI TERHADAP PRESTASI BELAJAR PADA ASKEB III (NIFAS) DITINJAU DARI MOTIVASI BELAJAR MAHASISWA DIII KEBIDANAN STIKES BINA SEHAT PPNI MOJOKERTO - Dewi Yanti, Ariu (JURNAL KEPERAWATAN SEHAT, 2015)
Learning Method is a way of presenting the material of general nature. In the learning process of learning methods very big influence on the achievement of learning objectives.This method was chosen because it was easily implemented and teachers was not require special tools and no need to design student activities. Analyzing the effect of a lecture than a demonstration of learning achievement in Askeb III (Postpartum), to analyze the effect of motivation on learning achieve mentat Askeb III (Post partum), to analyze the interaction effect of teaching methods and learning motivation on learning achieve mentat Askeb III (Post partum). This study used a quasi-experimental method (Quasi Experiment Design), with a time series design with a comparison group (Control Time Series Design). Samples used as many as 64 students.This research instrument was a recapitulation of learning achievement Askeb III, the observation sheet and competency testing practice. There was a significant difference compared to the lecture demonstration method of learning achievement Askeb III significance 0.000 <0.05. There was a significant difference compared to the high motivation of low motivation on learning achievement Askeb III with significance 0.001> 0.05. Interaction effect of teaching methods on learning achieve mentand motivation Askeb III. The first hypothesis test results showed that the value of F = 7.045 with a significance of 0.010> 0.05. There was a significant difference compared to the lecture demonstration method of learning achievement Askeb III yet and there was interaction effect of teaching methods on achieve mentand motivation to learn Askeb III.Keyword:Ceramah, Demonstrasi, Prestasi belajar, Motivasi belajar